PARENTS' ROLE AND CONSTRAINTS IN ACCOMPANYING THEIR CHILDREN TO STUDY DURING THE PANDEMIC COVID 19 - Zohiro Zohiro; Ridhah Taqwa; Ben Wadham; Firman Mansir; Abdullah Idi; Syarnubi Syarnubi (Tadrib: Jurnal Pendidikan Agama Islam, 2022)
This research aims to find out the role and what is being done by parents in accompanying children to learn during the Covid-19 pandemic. Parents who act as home learning executors must carry out the tasks arranged by the teacher at school. The role of parents as a substitute for the teacher is to convey the learning material that has been prepared. This type of field research uses qualitative descriptive methods. Data collection techniques were interviews, participant observation, and documentation. To determine the validity of the data, an examination technique is needed based on four criteria: the degree of trust (credibility), transferability, dependence, and certainty. The method used case studies through interviews with thematic analysis in some working parents, four parents as teachers, and five as housewives. The results show that, in general, the role of parents in the time of the covid-19 pandemic is to ensure children adopt clean and healthy living, establish intense communication, accompany children in doing schoolwork, provide education, and guide children during pandemic times. The obstacles parents face in accompanying children to learn during the pandemic are parents needing to become more familiar with children's subject matter, difficulties in operating gadgets, difficulty with internet networks, lack of patience in accompanying children, and limited time to accompany children.